Public Management and Food Security: The Role of Sustainable Entrepreneurship as a Development Strategy - Vega, Macarena Valladares-; Cano, César Alfredo Aguilar; Luna, Juan Carlos Rodríguez; Pinto, A. Carrillo (Journal of Posthumanism, 2025)
Food security has established itself as a priority on public agendas, especially in contexts of environmental, economic and social crisis. This article analyzes the role of sustainable entrepreneurship as a development strategy linked to public management to face contemporary food challenges. A mixed methodology is adopted, combining documentary analysis and semi-structured interviews with actors in the agri-food sector. The results indicate that an effective articulation between public policies, local entrepreneurship and sustainability can strengthen territorial food resilience. It is concluded that sustainable entrepreneurship is not only an economic driver, but also a key tool for more equitable food governance.